ANALYSIS OF STUDENTS' ABILITY IN VISUALIZING EDUCATIONAL PAPERS ON POWERPOINT - Pulungan, Husniah Ramadhani; Saputri, Nor Mita Ika; Purba, Happy Sri Rezeki; Al-mamri, Muhammed Jubran Naji; Suhery, Dedy (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze students' ability to visualize papers in PowerPoint. This is done so that students' obstacles in presenting educational PowerPoint can be found. The research method used is observation of 11 PowerPoint scripts that are student group assignments in the Scientific Paper Writing Course. The results obtained indicate that students' ability to visualize their papers in PowerPoint is divided into 7 categories of slide appearance and 12 errors in visualizing them. The research findings prove that there is a group that presents 127 slides or 52% in PowerPoint, even though that number has far exceeded the presentation of slides which should be around 10 to 12 slides. Meanwhile, the highest error of 22% is not presenting facts of phenomena as an important basis in the background. Thus, all of these findings can be used as evaluation material in the next learning process so that students can avoid mistakes and can present their paper visualizations in PowerPoint more educationally. In order to overcome this, it is necessary to prepare more mature, complete, and full independent practice materials so that the obstacles that arise can be resolved properly. The implications of this study can be a positive gap to improve the level of material with a more educational presentation. Thus, through a better understanding of the material, students will be able to visualize their papers into PowerPoint even better.